Effect of Equity Financing and Debt Financing on Company Profitability - Desman Serius Nazara; Deny Purwo Sambodo; Dede Hertina; Musran Munizu; Asri Ady Bakri (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
This study aims to determine and analyze effect of equity financing and debt financing on company profitability. This type of research to support data analysis in this study uses quantitative research. Population in this research is Telecommunications Companies that went public on the Indonesia Stock Exchange for the 2017-2022 period. There are 30 samples, of which there are 5 telecommunications companies listed on the Indonesia Stock Exchange until the 2022 period, and each company contributing 6 samples. To answer the research hypothesis, multiple linear regression analysis is used. The results show that equity financing has a significant effect on company profitability. Debt financing has a significant effect on company profitability.